A case of ingrown nail using buckle VHO‐Osthold® Perfect as a method of conservative treatment - Kuros, Faustyna; Wcisło‐Dziadecka, Dominika (Journal of cosmetic dermatology, 2021)
Background Ingrowing Nail is an ailment in the toe area. This problem is observed in 20% of the population, in all age groups, but most often occurs in teenagers and young adults. The process of ingrowing nail stimulates natural defense mechanisms of the body in the form of inflammation and severe pain. Aims The aim of this paper was to make the VHO‐Osthold® Perfect buckle effective as an alternative to nail plate surgery and to determine the patient's comfort during this method of treatment. Patients/Methods A descriptive case study conducted in a 15‐year‐old patient who had ingrowing nails in the big toes of both feet. Results It has been shown that the VHO‐Osthold® Perfect buckle therapy constitutes an effective method for ingrowing nails and one in a few conservative methods in orthonyxia, as an alternative to surgery. Conclusions The study and clinical experience confirm that the therapy of ingrowing nails with the VHO‐Osthold® Perfect buckle is painless and noninvasive. This treatment can be safely and effectively carried out by a qualified podiatrist or cosmetologist in podological practice.